The Use of Nearpod in Learning English: A Survey Study at Junior High School - Ardiansyah, Ahmad; Samtidar, Samtidar; Munir, Munir (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
This study investigates the use of Nearpod as a tool to enhance English and aims to examine students' perceptions of using Nearpod as a learning medium while learning English learning at SMPN 4 Sungguminasa. The findings reveal that Nearpod significantly aids students in improving their English skills, particularly writing, speaking, and vocabulary development. Its interactive features, such as quizzes and gamified activities, make learning more engaging and help students comprehend materials more effectively. Moreover, the app supports memory practice and fosters vocabulary expansion. Students' perceptions of Nearpod were divided into positive and negative. Those with positive perceptions highlighted its motivational, engaging, and task-supportive nature, along with its ability to create a competitive learning atmosphere. Conversely, some students expressed concerns over its reliance on internet connectivity, which limits accessibility in offline settings. Overall, Nearpod proves to be a valuable yet context-dependent resource for English learning.Keywords: perceptions, Nearpod, learning English